PENERAPAN METODE PEMBELAJARAN DRILL UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA JEPANG KEPERAWATAN BAGI MAHASISWA YANG AKAN BEKERJA KE JEPANG - Wismadewi, I Gusti Agung Galuh; Putu Rusanti; Ni Kadek Ary Susandi; Ni Wayan Novi Suryati; Ni Kadek Maya Cintya; I Putu Agus Endra Susanta (Journal of Practice Learning and Educational Development, 2025)
This study aims to assess the effectiveness of the drill method in improving Japanese speaking skills in nursing for students who plan to work in Japan. The subjects of this study were 36 students from the Undergraduate Nursing and Midwifery Program at ITEKES Bali, who attended the Japanese Language Center class in the 2023/2024 academic year. The method used was descriptive qualitative, with data collection techniques such as questionnaires, interviews, and observations. The results showed that most students had difficulty in mastering and pronouncing nursing-related vocabulary in Japanese and showed low learning motivation. The application of the drill method, which emphasizes repeated practice through conversation or role-playing, was proven to be effective in helping students remember and pronounce vocabulary correctly. These findings confirm that the drill method is effective in improving speaking skills and motivation to learn Japanese for nursing purposes. Based on the results of the questionnaire, out of 36 students, 32 showed motivation to learn Japanese, while only 4 reported lack of motivation, generally due to uncertainty about work in Japan. This motivation is influenced by internal and external factors. Students who have high motivation to work in Japan show greater enthusiasm for learning the language. It is hoped that this study can be a reference for educators in choosing appropriate and innovative teaching strategies.